ARE ISLAMIC STOCKS LESS EXPOSED TO SENTIMENT-BASED MISPRICING THAN NON-ISLAMIC ONES? EVIDENCE FROM THE INDONESIAN STOCK EXCHANGE - Rizqi Umar Al Hashfi; Ahmad Maulin Naufa; U’um Munawaroh (Journal of Islamic Monetary Economics and Finance, 2021)
The aim of this research is to verify the role of Islamic value in stock mispricing in the Indonesian capital market. Empirically, high investor sentiment can lead to mispricing on equity appraisal. When investors feel excessively optimistic about their valuation, equity will be overpriced, or vice versa. The presence of Islamic values, such as the prohibition of interest, speculative and uncertain transactions, and excessive leverage, arguably reduce sentiment-based mispricing. Daily and cross-sectional market data were employed. In addition, principal component analysis was conducted to construct a firm-specific investor sentiment variable. With regard to the method, the Hausman-Taylor (H-T) approach was used to deal with heterogeneity, endogeneity, and the time-invariant variable in Fama-MacBeth regression. The results show that our baseline analysis confirms the mispricing of overall stocks. However, Islamic stocks are less exposed to sentiment-based mispricing than their non-Islamic counterparts. The results are consistent with our robustness test, in which we estimate the equation model across industry and portfolio. Finally, our findings imply various insights for both investors and policymakers.